Geographic variation in genetic composition, sexual communication and mating compatibility of the False Codling Moth, Thaumatotibia leucotreta for optimisation of area-wide control - Aigbedion-Atalor, Pascal; Heiduk, Annemarie; Upfold, Jennifer; Shuttleworth, Adam; Moore, Sean; Hill, Martin; Coombes, Candice (Frontiers in Ecology and Evolution, 2024)
Intraspecific variation of sex pheromone is a driver of reproduction isolation and speciation in insects. The False Codling Moth (FCM) Thaumatotibia leucotreta (Lepidoptera: Tortricidae) is a quarantine pest endemic to sub-Saharan Africa (SSA). The currently available precision control measures for FCM are based on female sex pheromone components that lure males into traps. However, the existing data on the composition of the female sex pheromone, especially the isomer ratios of the main pheromone component (E/Z)-8-dodecenyl acetate, are inconsistent for populations in SSA. This inconsistency led to speculation about possible reproductive isolation between geographically separated FCM populations and the potential need for local adjustment of pheromone-based FCM control tools. Any adjustment, however, requires a comparative evaluation of geographic variation in FCM sexual communication and inter-population mating compatibility. We investigated genetic isolation and mating compatibility between five geographically isolated FCM populations in South Africa. These populations were found to separate into three genetically distinct groups, and in mating compatibility tests males preferred females of their own population when given choices; without a choice, however, males mated with females from all other populations and successfully transferred spermatophores to these females. The ratio of (E)-and (Z)-8dodecenyl acetate was similar (c. 4:1) across all studied South African populations, indicating that this main female pheromone component does not cause the observed intra-population mating preferences. It remains to be investigated if qualitative/quantitative variation in other sex pheromone components influences intra-population recognition in South African FCM, providing a base for the development of regionally-specific lures for area-wide control programmes.